A compact triple-notch band ultra-wideband antenna - Abdul Rashid, Munirah Az Zahra; Mohd Shah, Shaharil; Ponniran, Asmarashid (HRPub, 2019)
This paper proposed a compact ultra-wideband (UWB) antenna (17.5 × 20.5 mm2) with a triple-notch band characteristic to overcome the interference caused by the three narrow frequency bands that coexist within the ultra-wideband frequency ranging from 3.1 to 10.6 GHz as stipulated by the Federal Communication Commission (FCC). Two slots on the radiating patch and a copper trace on the ground plane of the antenna were introduced to reject the WiMAX, WLAN and SHF frequency bands. The dimensions of the slots and copper trace are optimized to achieve the desired band rejections. The compact size of the antenna is in line with the miniaturization requirement of modern wireless communication devices but at the same time is able to support multiple wireless communication services. The simulation result shows that the antenna can function over the UWB frequency range but with band rejections on the WiMAX band (from 3.2 GHz to 3.6 GHz, WLAN band) (from 5.15 GHz to 5.85 GHz) and SHF band (from 7.25 GHz to 8.395 GHz). The proposed antennas are simulated and designed in CST Microwave Studio® software and fabricated on a FR-4 substrate with a relative dielectric constant, εr of 4.5, loss tangent, tan δ of 0.019 and thickness, h of 1.6 mm.